2021
DOI: 10.1021/acs.jctc.1c00693
|View full text |Cite
|
Sign up to set email alerts
|

One-to-One Correspondence between Reaction Pathways and Reactive Orbitals

Abstract: The one-to-one correspondence between reaction pathways in the potential energy theory and reactive orbitals in the electronic theory for reactions is presented. In this study, the reactive orbital energy method is applied to the intrinsic reaction coordinates of the global reaction route map generated by an automated reaction path search method. The reactive orbital energy method specifies the pairs of occupied and unoccupied reactive orbitals driving chemical reactions and determines whether the reactions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…The ROET analyses are performed using the calculated IRCs of the reaction paths and the MO energies at the geometries on the IRCs as follows 10,15 : Plotting the valence orbital energies for each IRC, the orbital energies are, first, traced along the IRCs for three reaction processes: reactant complex to product complex, reactant molecules to reactant complex, and product complex to product molecules. In our original orbital energy‐tracing program, the MO giving the maximum overlap between the succeeding points is automatically picked out, while if the picked orbital would be multiplicated, the orbital giving the minimum orbital energy gradients for the orbital energies at the anteroposterior steps is selected. The occupied and unoccupied valence orbitals giving the most stabilized (decreased) and most destabilized (increased) orbital energies are then chosen for the orbital energies traced along the IRC of the reaction process between the reactant and product complexes as the occupied and unoccupied reactive orbitals.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ROET analyses are performed using the calculated IRCs of the reaction paths and the MO energies at the geometries on the IRCs as follows 10,15 : Plotting the valence orbital energies for each IRC, the orbital energies are, first, traced along the IRCs for three reaction processes: reactant complex to product complex, reactant molecules to reactant complex, and product complex to product molecules. In our original orbital energy‐tracing program, the MO giving the maximum overlap between the succeeding points is automatically picked out, while if the picked orbital would be multiplicated, the orbital giving the minimum orbital energy gradients for the orbital energies at the anteroposterior steps is selected. The occupied and unoccupied valence orbitals giving the most stabilized (decreased) and most destabilized (increased) orbital energies are then chosen for the orbital energies traced along the IRC of the reaction process between the reactant and product complexes as the occupied and unoccupied reactive orbitals.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We have found no other orbital pairs, which are needed to represent the reactions in the present ROET analyses. Based on the above‐mentioned one‐to‐one correspondence between the reactive orbital pairs and reaction pathways, 15 we consider that the main occupied and unoccupied orbital pair drives each reaction pathway and that the orbitals of equivalent orbital energy variations are subject to the main orbital pair. We should also think of subsequent barrierless reaction processes that might connect to the main processes.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FJK framework is general enough to be applicable to situations where magnitude of a complicated process can be estimated with a relatively simple orbitalbased descriptor. 69,70 Further applications were beyond the scope of this work and are part of future work. At the same time, we observed that for a poor choice of a Slater determinant pair representing the change of electronic structure FJK may be less accurate than conventional representations, as exemplified by QM7b's first excitation energies.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%